2013
DOI: 10.1002/prot.24445
|View full text |Cite
|
Sign up to set email alerts
|

Role of histidine for charge regulation of unstructured peptides at interfaces and in bulk

Abstract: Histidine rich, unstructured peptides adsorb to charged interfaces such as mineral surfaces and microbial cell membranes. At a molecular level, we investigate the adsorption mechanism as a function of pH, salt, and multivalent ions showing that (1) proton charge fluctuations are -in contrast to the majority of proteins -optimal at neutral pH, promoting electrostatic interactions with anionic surfaces through charge regulation, and (2) specific zinc(II)-histidine binding competes with protons and ensures an unu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(65 citation statements)
references
References 55 publications
1
61
0
Order By: Relevance
“…34 Moreover, the surface curvature and chain persistence length also influence the adsorption process as studied by Kampmann et al for semi-flexible polymers. [41][42][43] The self-organization of proteins adsorbing on surfaces is shown to cause density inhomogeneities in the surface distribution of proteins. 36 All these theoretical studies are of main importance to explain, for instance, the length of wrapped DNA around histones in terms of the binding energy to histone cores and elastic energy penalty of DNA wrapping.…”
Section: Introductionmentioning
confidence: 99%
“…34 Moreover, the surface curvature and chain persistence length also influence the adsorption process as studied by Kampmann et al for semi-flexible polymers. [41][42][43] The self-organization of proteins adsorbing on surfaces is shown to cause density inhomogeneities in the surface distribution of proteins. 36 All these theoretical studies are of main importance to explain, for instance, the length of wrapped DNA around histones in terms of the binding energy to histone cores and elastic energy penalty of DNA wrapping.…”
Section: Introductionmentioning
confidence: 99%
“…Do "cryptic" amino acid substitutions diminish net charge by a single unit, or more or less than expected because of "charge regulation"? 19,20 Do ALSvariant SOD1 proteins follow the same nonlinear electrostatic pathway during metal loading as the WT protein and do they regulate net charge across subcellular pH? 21 Charge regulation is a process by which the pK a of a protein's functional groups undergo cooperative increases or decreases to compensate for electrostatic perturbations within the interdependent network of ionizable residues.…”
Section: Introductionmentioning
confidence: 99%
“…They found that zinc(II)-histidine binding competes with protons and ensures a constant charge distribution over a broad pH interval. 45 Hytonen et al discuss the role of protein conformation in the regulation of cell-matrix adhesion with a spotlight on the role of IDPRs. They highlight several proteins, such as focal adhesion kinase (FAK) and vinculin, where the IDPRs present in these proteins modulate conformation thereby modulating cellmatrix adhesion.…”
Section: Analyzing Functions Of Idps and Idprsmentioning
confidence: 99%